ACETYLSALICYLIC ACID: DO WE KNOW EVERYTHING ABOUT IT AND ITS PROPER USE? - S. A. Boldueva; I. A. Leonova (Столичная издательская компания, 2015)
Use of acetylsalicylic acid (ASA) in cardiology practice is presented. ASA modes of action and the main indications are discussed. ASA use for primary cardiovascular diseases prevention and its possible side effects are considered especially. Peculiarities of ASA use in specific clinical situations, and some pleiotropic effects are also presented.